1986
DOI: 10.1139/f86-222
|View full text |Cite
|
Sign up to set email alerts
|

Plankton Size Spectra in Relation to Ecosystem Productivity, Size, and Perturbation

Abstract: Quantification and comparisons of the structure of open-water plankton communities from 25 inland lakes of Ontario, from the Laurentian Great Lakes Superior, Huron, St. Clair, Ontario, and Erie, and from the Central Gyre in the North Pacific Ocean were made on the basis of the normalized biomass size spectrum. Residual variation around the fitted straight lines (corresponding to a theoretical steady state) was least for the large, oligotrophic Lake Superior and the North Pacific Gyre and greatest for eutrophic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
297
5
7

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 385 publications
(333 citation statements)
references
References 10 publications
24
297
5
7
Order By: Relevance
“…For this reason, ecologists try to find means for quantitative estimations of structural deformation for natural communities (Odum 1971;Begon et al 1996). Size spectrum analysis (Sheldon et al 1972;Sprules & Munawar 1986) is one of the tools available to characterize the whole community structure. The 'ataxonomic' biomass size spectrum (BSS) and normalized biomass size spectrum (NBS) are closely connected to a more traditional one, where the size-frequency distribution of species or higher taxa is plotted (Hemmingsen 1934;Hutchinson & MacArthur 1959;Smith et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, ecologists try to find means for quantitative estimations of structural deformation for natural communities (Odum 1971;Begon et al 1996). Size spectrum analysis (Sheldon et al 1972;Sprules & Munawar 1986) is one of the tools available to characterize the whole community structure. The 'ataxonomic' biomass size spectrum (BSS) and normalized biomass size spectrum (NBS) are closely connected to a more traditional one, where the size-frequency distribution of species or higher taxa is plotted (Hemmingsen 1934;Hutchinson & MacArthur 1959;Smith et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…When the slope of the log-transformed spectrum is Ϫ1.0, there is an even distribution of biomass among all size classes-the situation observed by Sheldon and co-workers (Sheldon et al 1972(Sheldon et al , 1977-that has invited explanation for some time (e.g., Platt and Denman 1978;Kiefer and Berwald 1992). Many studies have shown that, regardless of slope, a log-linear model appropriately characterizes planktonic spectra (e.g., Rodriguez and Mullin 1986;Ahrens and Peters 1991), although not equally well in all situations (e.g., Sprules et al 1983;Tittel et al 1998). Rodriguez and Mullin (1986) argued that the significance of power-law descriptions of size spectra per se may be of more value than a detailed analysis of slopes.…”
mentioning
confidence: 95%
“…Sprules and Munawar (1986) A similar difference between energy partitioning patterns in stable versus unstable ecosystems can be traced within separate trophic groups. Biddanda et al (2001) measured bacterial respiration in Lake Superior and several small Minnesota lakes, differing greatly in the degree of eutrophy (chlorophyll content from 0.57 to 53 g l −1 ).…”
Section: Size Spectra In Aquatic Ecosystemsmentioning
confidence: 93%